2022
DOI: 10.1080/0142159x.2022.2104700
|View full text |Cite
|
Sign up to set email alerts
|

Editing the editors: Aims and priorities of health professions education journals

Abstract: Purpose: Although health professions education (HPE) scholarship has flourished in recent decades, the influence of HPE journals has received little attention. This study examines the editorial policies and priorities of leading HPE journals. Methods: Fourteen HPE journals with the highest impact factors were reviewed for their editorial aims, scope, intended readership, and priority topic areas. Text from journal websites was coded using thematic analysis. Results: 10/14 HPE journals included in this study we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(21 reference statements)
2
0
0
Order By: Relevance
“…As such, we would not necessarily expect these author characteristics to change over time. However, similar to Arfeen and colleagues' findings, we observed that the majority of the journals examined here explicitly describe themselves as ‘international’ in focus 58 . That said, our data align with other studies 5,58 indicating that most do not at present publish a diverse representation of authors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As such, we would not necessarily expect these author characteristics to change over time. However, similar to Arfeen and colleagues' findings, we observed that the majority of the journals examined here explicitly describe themselves as ‘international’ in focus 58 . That said, our data align with other studies 5,58 indicating that most do not at present publish a diverse representation of authors.…”
Section: Discussionsupporting
confidence: 91%
“…However, similar to Arfeen and colleagues' findings, we observed that the majority of the journals examined here explicitly describe themselves as ‘international’ in focus 58 . That said, our data align with other studies 5,58 indicating that most do not at present publish a diverse representation of authors. Additionally, it is important to note that Global South authors may decide not to publish in these journals for reasons beyond (or unrelated to) epistemic injustice.…”
Section: Discussionsupporting
confidence: 91%